Synthesis of Ni/NiAlOx Catalysts for Hydrogenation Saturation of Phenanthrene - Liu, Dao-Cheng; Chen, Yu; Jing, Jie-Ying; Rajendran, Antony; Bai, Hong-Cun; Li, Wen-Ying (Frontiers in Chemistry, 2021)
The saturation of octahydrophenanthrene was the rate determining step in the hydrogenation process from phenanthrene to perhydrophenanthrene, which was due to the steric hindrance and competitive adsorption of octahydrophenanthrene. In this work, a series of Ni/NiAlOx catalysts with uniform electron-deficient state of Ni derived from nickel aluminate structure was synthesized to overcome the disadvantage of noble catalyst and the traditional sulfided catalysts in the saturation hydrogenation process of phenanthrene. Results showed that the catalyst calcinated at 650 °C possessed more Ni2+ (~98%) occupying octahedral sites and exhibited the highest robs (1.53×10-3 mol·kg-1·s-1) and TOF (14.64×10-3 s-1) for phenanthrene hydrogenation. Furthermore, its ability to overcome steric hindrance and promote rate determine step was proven by octahydrophenanthrene hydrogenation. Comparing the evolution of hydrogenation activity with the change in the electronic structure of surface Ni sites, it was shown that the increase of metallic electron deficiency hindered the π-back bonding between surface Ni and aromatic rings, which was unfavorable for aromatic adsorption. As a result, the phenanthrene hydrogenation saturation performance can be enhanced by stabilizing the electron deficient state of surface Ni on an optimal degree.